MEDIA SOSIAL DAN DAMPAKNYA TERHADAP PERCERAIAN - Sohrah Sohrah (Al-Risalah, 2020)
Lately, the use of social media is increasingly prevalent after experiencing the development of its characteristics and uniqueness. The convenience offered by social media for its users also influences one's lifestyle. The results of this study conclude that the presence of social media contributes to the rift of households for some married couples which is marked by an increase in divorce rates triggered by disputes and quarrels for married couples. The results showed that there were several cases as proof of the role of social media as one of the causes of divorce due to the husband or wife so easily covert infidelity because of the use of social media. It is undeniable that the presence of social media as a communication tool has a very important positive side in this modern era to facilitate various interests and needs of human life, but on the other hand there are also negative sides that can affect the morale of its users. One impact that has been rife lately is the high number of divorce cases as reported by the Makassar Religious Court office from 2015-2018. In 2015 there were 493 cases, while in 2018 there were 628 cases. These cases were caused due to ongoing disputes.